Light-nutrition coupling effect of degradable fluorescent carbon dots on lettuce. Issue 2 (25th January 2023) - Pan, Xiaoqin; Fu, Fangmei; Xie, Zhenxi; Li, Wei; Yang, Xian; Kang, Yunyan; Qu, Songnan; Zheng, Yinjian; Li, Qingming; Zhang, Haoran; Song, Shiwei; Lei, Bingfu
Abstract : Degradable fluorescent N-doped CDs are oxidized and degraded into substances that can be used for lettuce growth. Their excellent light conversion characteristics promote the utilization of the CD degradation products by lettuce. Abstract : The increasing application of carbon dots (CDs) inevitably leads to environmental leakage. To be environmentally friendly, degradable CDs will become a mainstream agricultural application in the future. We prepared three CDs with different functional groups. Fourier transform infrared spectroscopy (FTIR) and X-ray photoelectron spectroscopy (XPS) analysis showed that –CC–H and CO groups on the CD surfaces are major sites for oxidative degradation of the CDs. The pyridine N is responsible for photoproduction of ˙OH and ˙O2 −, which will self-induce degradation. By liquid chromatography-mass spectrometry (LC-MS) method, the routes for N-doped CDs degrading into carboxylic acid compounds, CO2, NH4 +, and H2 O are clearly illustrated. After spraying fluorescent CDs on lettuce leaves, only the group of lettuce that combined the light conversion function of N3-CDs and the final degradation products of N3-CDs exhibited a significant enhancement of the net photosynthesis rate by 1.13 times, acceleration of the ETR by 1.19 times, and improved expression of genes related to CO2 fixation in the C4 cycle and carbon assimilation in the C3 cycle.